A Review of Heavy Metal Contamination of Food Crops in Nigeria - Michael Monday Onakpa; Anoka Ayembe Njan; Ogbureke Chidiebere Kalu (Ubiquity Press, 2018)
Heavy metal contamination of food crops is an issue of global concern that ultimately results in toxicity and diseases in humans and animals through consumption of contaminated soils and food crops. With a population of 182 million people, Nigeria is regarded as the most populous country in Africa. The people suffer environmental pollution from high levels of heavy metal accumulation in the environment and in food crops. Heavy metals have atomic densities higher than 4 g/cm3, and these include lead (Pb), cadmium (Cd), zinc (Zn), mercury (Hg), arsenic (As), silver (Ag), chromium (Cr), copper (Cu), iron (Fe), and platinum (Pt). The high level of environmental contamination by these metals is dangerous because their uptake by plants and subsequent accumulation in food crops consumed by humans and animals is deleterious to health. There are many known sources of harmful metals, including the earth, which releases them into food, air, and water, and anthropogenic activities, such as the application of fertilizer in agriculture, the use of pesticides and herbicides, and irrigation. Other sources are automobile emissions, paints, cigarette smoking, industries, and sewage and waste disposal. Evidence shows that vegetables and other food crops consumed in Nigeria are contaminated by heavy metals, and this is associated with adverse health issues, such as cancer, which is currently on the rise in Nigeria. It is therefore vital that communities with high levels of heavy metal pollution avoid eating large quantities of these food items. There is also the need for the monitoring of levels of these injurious elements in food crops.